Mini-FLOTAC and McMaster egg counting method for detection of gastrointestinal parasites in small ruminants: a comparison study - Vieira, Osires Lustosa; Macedo, Lucia Oliveira; Bezerra-Santos, Marcos Antônio; Santos, Lucas Azevedo dos; Mendonça, Carla Lopes de; Alves, Leucio Câmara; Ramos, Rafael Antonio do Nascimento; Carvalho, Gílcia Aparecida de (Medicina Veterinária, 2021)
The proper diagnosis of gastrointestinal parasites of small ruminants requires the development of multivalent techniques characterized by high sensitivity, specificity, precision, reproducibility, and the ability to quickly detect and monitor infections that pose risks to animal health. The aim of this study was to evaluate the performance of Mini-FLOTAC technique and McMaster egg counting (gold standard) in the detection of gastrointestinal parasites of goats and sheep. A total of 789 fecal samples were analyzed (401 of sheep and 388 of goats). From those, nematode eggs were detected in 80.86% (638/789), being 72.57% (291/401) from sheep and 89.43% (347/388) from goats. The Mini-FLOTAC technique presented a better performance to detect helminth eggs in both goats (88.40%; 343/388) and sheep (71.57%; 287/401) (?2 = 10.358; p < 0.0001). Kappa analysis revealed a weak concordance between techniques for goats (k = 0.342; p < 0.001) and sheep (k = 0.281; p < 0.001). Data herein reported suggests that the Mini-FLOTAC is a technique more sensitive than the McMaster egg counting, therefore its use might be adopted for the diagnosis of gastrointestinal infection in small ruminants.